Reconfiguration transculturelle du «Roi grenouille» : processus scripturaires et réception - Charnay, Bochra (Ondina - Ondine, 2018)
King Frog is an uncommon tale in its adaptations as a book for children — it is still more uncommon in its translations for young readers on the other side of the Mediterranean. Yet a corpus has been gathered in order to explore from the angle of polyphony and cultural reinvestments. We will see how those books, wavering between the discovery of different culture and its appropriation by the welcoming culture, reconfigure Grimm’s text and how the illustrations reveal these two interests. Our attention, of course, will focus on the meaning of the text and its cultural values as well as on the scriptural methods which re-actualise it, Also the question whet ther,we witness a real method of acculturation or a mere method of transmission will be addressed. Key Words: Rewriting, transcultural, polyphony, acculturation, iconic overstatement